1990
DOI: 10.1161/01.cir.82.6.1962
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of propranolol, diltiazem, and nifedipine in the treatment of ambulatory ischemia in patients with stable angina. Differential effects on ambulatory ischemia, exercise performance, and anginal symptoms. The ASIS Study Group.

Abstract: Entry criteria were a positive exercise treadmill test during placebo therapy characterized by 1.0 mm or more ST segment depression and angina pectoris, and six or more episodes of transient ST segment depression of 1.0 mm or more on a 48-hour ambulatory electrocardiogram. One hundred ninety-four patients were screened, 63 were eligible and received randomized therapy, of which 56 patients completed at least two of the four treatment periods and were included in an intent-to-treat analysis. Fifty patients comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(26 citation statements)
references
References 55 publications
(5 reference statements)
2
24
0
Order By: Relevance
“…Nifedipine, a short-acting dihydropyridine calcium antagonist, has been reported to cause reflex sympathetic stimulation and tachycardia when blood pressure decreases after the administration of the drug (14,15). Amlodipine, a long acting calcium antagonist, is characterized by a higher vascular selectivity and smaller positive inotropic effect; therefore, amlodipine is recommended for patients with hypertension and angina (8).…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine, a short-acting dihydropyridine calcium antagonist, has been reported to cause reflex sympathetic stimulation and tachycardia when blood pressure decreases after the administration of the drug (14,15). Amlodipine, a long acting calcium antagonist, is characterized by a higher vascular selectivity and smaller positive inotropic effect; therefore, amlodipine is recommended for patients with hypertension and angina (8).…”
Section: Discussionmentioning
confidence: 99%
“…A number of biological activities have also been associated with it, such as antianginal [8], antihypertensive [9], antiischemic [10], antiarrhythmic [11], platelet aggregation inhibitor [12], vasodilator [13], calcium channel blocker [14], calcium channel antagonist [15] and calcium channel activator [16]. In recent past, under the frame work of "Green Chemistry" microwave-assisted synthesis is one of the non-conventional techniques used in laboratory for the synthesis of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] As for medication, Juul-Moller et al, reported the efficacy of aspirin in patients with stable AP, 17 and Pepine et al showed the efficacy of atenolol, even in patients with silent myocardial ischemia. 19 Many recent clinical trials support the effectiveness of statins.…”
Section: Prognosis Of Asymptomatic Cadmentioning
confidence: 99%